Obesity and binge eating disorder - Munsch, Simone 1970-; Beglinger, Christoph 1950- (Karger, 2005)
Overweight and obesity have quite recently become a major problem affecting many countries worldwide. This publication gives a comprehensive overview on the current knowledge of the pathophysiological mechanisms in the regulation of hunger and satiety. An insight into the important facets of symptomatology, epidemiology, etiology and the treatment of obesity and BED in adults is given and in one chapter the pros and cons of designating BED as a disorder are discussed. The interaction of biological, sociological and psychological factors in the development and maintaining of obesity and BED as well as treatment options both from the medical and from the psychological viewpoints are outlined. An exclusive overview on the prevalence rates, symptomatology, course and treatment approaches of obesity and BED in childhood is presented.General physicians as well as psychologists, pediatricians and psychiatrists interested in obesity and BED in children and adults will find in this book an excellent overview of the latest research
new insights into a complex disorder
Keywords: Psychotherapie; Psychiatry; Internal Medicine; Gastroenterology; Nutrition; Obesity; Psychology; Psychopathology; Psychotherapy; Fettsucht; Binge-eating Disorder; Aufsatzsammlung